Analysing the Epidemiological Factors and Biological Markers of Rheumatoid Arthritis - Kumar, Sanjay; Bharti, Ajay; Gupta, A. K.; Saini, Hemraj (Recent Developments in Medicine and Medical Research Vol. 15, 2021)
Background: Early diagnosis is critical in the management of rheumatoid arthritis because it allows for timely intervention and a better outcome. A prospective study was conducted to investigate epidemiological factors and biological markers of rheumatoid arthritis, as well as NEW ACR 2010 criteria and DAS28, with the goal of early diagnosis and reduced morbidity. Material and Methods: Based on the new ACR 2010 criteria, 62 patients between the ages of 21 and 75 years old with various rheumatoid arthritis complaints were included in this study. The following factors were observed: age and gender distribution, disease duration, seasonal variation, socioeconomic status, pain in various joints, presentation with deformity and its interval from disease onset, various biological markers (RA factor, antiCCP), disability score (das28), and VAS. Results: The most common age group was 41-50 years, with a female-male ratio of 4:1, and the disease was most commonly diagnosed within 24 months of onset and during the winter. Wrist and MCP > PIP > Elbow, Shoulder, and Knee > Ankle >Cervical >Lumbar spihe was the most common pattern of joint involvement. 28 joint involvement as DAS28 was seen in 69.35 percent of patients, while 19.36 percent had classic deformity.RA factor was positive in 64.52% and Anti-CCP in 72.7% of RA factor negative cases The average DAS28 score was 7.38, and 53.23 percent had a NEW ACR 2010 score of 9. Conclusion: Anti-CCP can be used to diagnose RA negative cases, but when combined with the DAS28 and NEW ACR 2010 scores, the accuracy of diagnosing rheumatoid arthritis improves and early treatment can be given, improving the outcome and decreasing morbidity.